An empirical examination on the determinants of IPO underpricing in China - He, Wanqiu (2018)
This dissertation examines the determinants of IPO underpricing based on the A-share IPO market in China. Using a sample of 2079 firms’ IPO information over the period of 2007 to 2017. An OSL regression model is established to test 6 main theories that explain the underpricing phenomenon, including the information asymmetry, ex ante uncertainty, time interval, ownership, issue of “hot and cold market” and speculative bubble and information cascades effect theory. This model is comprised of one dependent variable, initial return, which measures the level of IPO underpricing and 13 independent variables that include the IPO size, market capital value, number of employees, firms’ age, leverage ratio, earnings per share, underwriter fees, return on equity, time interval, issue of “hot and cold market”, inside holding rate, circulation rate and lottery winning rate. In the result of these variables, three variables (number of employees, earnings per share and lottery rate) are insignificant to the magnitude of underpricing and four variables demonstrate opposite relationships compared to original hypotheses.